2009
DOI: 10.1097/hjh.0b013e32832a6e39
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal interval between successive home blood pressure readings using an automated oscillometric device?

Abstract: Objectives-To clarify whether a shorter interval between three successive home blood pressure (HBP) readings (10 s vs. 1 min) taken twice a day gives a better prediction of the average 24-h BP and better patient compliance.Design-We enrolled 56 patients from a hypertension clinic (mean age: 60 ±14 years; 54% female patients). The study consisted of three clinic visits, with two 4-week periods of self-monitoring of HBP between them, and a 24-h ambulatory BP monitoring at the second visit. Using a crossover desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 28 publications
(26 reference statements)
0
31
0
Order By: Relevance
“…When head-to-head comparisons among clinic BP, HBP, and ABP have been performed [19,20,22], the level of agreement was not very good [19,20] or differed by age or sex [22], which could be because of the white coat effect or a device-specific effect. In this study, a pronounced white coat effect was not observed, perhaps because office BP was rigorously measured following the international guidelines after at least 5-min rest, measured by a physician postdoc rather than by a more senior doctor, and multiple measurements (more than six readings) were taken in one occasion after seeing a doctor [17]. The fact that BP levels were on average in the prehypertension range may also explain why office BP did not consistently exceed ABP [17].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…When head-to-head comparisons among clinic BP, HBP, and ABP have been performed [19,20,22], the level of agreement was not very good [19,20] or differed by age or sex [22], which could be because of the white coat effect or a device-specific effect. In this study, a pronounced white coat effect was not observed, perhaps because office BP was rigorously measured following the international guidelines after at least 5-min rest, measured by a physician postdoc rather than by a more senior doctor, and multiple measurements (more than six readings) were taken in one occasion after seeing a doctor [17]. The fact that BP levels were on average in the prehypertension range may also explain why office BP did not consistently exceed ABP [17].…”
Section: Discussionmentioning
confidence: 85%
“…In this study, a pronounced white coat effect was not observed, perhaps because office BP was rigorously measured following the international guidelines after at least 5-min rest, measured by a physician postdoc rather than by a more senior doctor, and multiple measurements (more than six readings) were taken in one occasion after seeing a doctor [17]. The fact that BP levels were on average in the prehypertension range may also explain why office BP did not consistently exceed ABP [17]. Another reason could be a device effect.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The significant correlation of having a job with home BPV could be because of higher physical activity by the employed patients compared with the patients without a job, or with inconsistent resting times before the HBP measurement [26] (i.e. a shorter resting time when an employed patient is pressed for time in the morning).…”
Section: Factors Associated With Bpvmentioning
confidence: 96%
“…The clinic BP was measured using a validated cuff oscillometric device (HEM-5001; Omron Healthcare, Kyoto Japan [18]) after the patients had rested for at least 5 min in the sitting position. Noninvasive ABPM was performed on a weekday with automatic devices (TM-2425 or TM-2430, A&D Co Inc, Japan [19,20]) that recorded the BP and pulse rate every 30 min for 24 h. The ABPM was performed at enrollment and after 6th month of treatment.…”
Section: Study Participantsmentioning
confidence: 99%